Seasonal life cycle of Pintomyia longiflocosa (Diptera: Psychodidae) under semi-controlled conditions in the Huila state, Colombia. - Jennifer Alejandra Vargas Durango; Gelys Igreth Mestre Carillo; Erika Santamaria Herreño; Miguel Angel Beltran Ruiz; Angela Cristina Zapata Lesmes; Astrid Geovana Muñoz Ortiz; Jesús Eduardo Escobar Castro (Public Library of Science (PLoS), 2024)
Background Pintomyia longiflocosa is considered a vector of etiological agents of cutaneous leishmaniasis. The objective of this research was to establish the parameters of the life cycle of Pi. longiflocosa in semi-controlled conditions in a rural area of the Campoalegre municipality, Huila, Colombia. Methodology/principal findings The life cycle of individuals of Pi. longiflocosa, obtained from two cohorts of collected, fed, and individualized females, was monitored during two different times of the year (between February and August 2020 and between July 2020 and January 2021, respectively). Determining parameters associated with the fertility and fecundity, time and attributes of development and survival, and its association with abiotic variables. The average duration of Cycle 1 (C1) and Cycle 2 (C2) was 134.9 and 148.78 days, respectively. The gonotrophic cycle of parental females presented significant differences (p-value <0.05) between C1 and C2 (8.47 and 11.42 days) as well as between fecundity and fertility parameters. The number of days it takes the development of the immature stages between the two cycles studied, also showed significant differences in the larvae II (15.21 and 22.23), larvae III (11.93 and 17.56), and pupae (24.48 and 22.9) stages. During C1, the survival rate was higher and consistent with the productivity of adult individuals (F1), compared to C2. Fecundity and fertility values were significantly higher in C2. Finally, a significant correlation between the number of individuals and temperature was evidenced in C1 while, for C2, there was a negative correlation with precipitation. Conclusions/significance Significant differences were found in several biological and reproductive parameters between the two cycles monitored. The parameters of the life cycle of Pi. longiflocosa in its natural habitat would be influenced by environmental factors related to the annual seasonality in the sub-Andean rural area, conditioning the temporal distribution of this species and, consequently, the possible transmission of causative agents of cutaneous leishmaniasis.